2022
DOI: 10.17219/acem/144134
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on pancreatic cancer surgery: A high-volume Polish center experience

Abstract: Background. A total of 148 surgeries were performed in our center on patients with pancreatic cancer in 2020. In 2019, 263 such procedures were performed (77.7% more) in this facility. Objectives.To analyze the impact of coronavirus disease 2019 (COVID-19) on pancreatic cancer surgery type, number and outcome in our center. Materials and methods.Retrospective data analysis of medical documentation in a hospital database from January 2019 till December 2020.Results. In 2020, we observed an increase of tumors lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
3
1
1
Order By: Relevance
“…Previous surgical studies have indicated that pancreatic surgery should be considered carefully for some special groups of patients with COVID-19, particularly those with positive symptoms, ensuring appropriate hospitalization duration. 25 Kędzierska-Kapuza et al 25 revealed an average postoperative hospitalization of 15.8 days, whereas our study showed longer average hospital stays of 24.7 days and 21.8 days for surgeries performed within 0-2 weeks and 2-4 weeks after infection, respectively. Therefore, our findings suggest a potential correlation between the time interval from infection to surgery and the length of hospital stay in patients infected with SARS-CoV-2.…”
Section: Discussioncontrasting
confidence: 55%
“…Previous surgical studies have indicated that pancreatic surgery should be considered carefully for some special groups of patients with COVID-19, particularly those with positive symptoms, ensuring appropriate hospitalization duration. 25 Kędzierska-Kapuza et al 25 revealed an average postoperative hospitalization of 15.8 days, whereas our study showed longer average hospital stays of 24.7 days and 21.8 days for surgeries performed within 0-2 weeks and 2-4 weeks after infection, respectively. Therefore, our findings suggest a potential correlation between the time interval from infection to surgery and the length of hospital stay in patients infected with SARS-CoV-2.…”
Section: Discussioncontrasting
confidence: 55%
“…A comparative mortality study covering 28 countries of the European Union predicted that pancreatic cancer will surpass breast cancer by 2025 (there will be more deaths from pancreatic cancer than from breast cancer, while the number of pancreatic cancer deaths will increase by 25%), whereby pancreatic cancer will be the third leading cause of cancer death by 2025 (after lung cancer and colorectal cancer) [5]. It remains a question of what effect the COVID-19 pandemic will have on the burden of pancreatic cancer, since previous findings were not consistent: while the findings of a retrospective multicenter cohort study showed that there were no changes in clinical presentation, treatment strategies and survival of pancreatic cancer during the SARS-CoV-2 outbreak [6], some studies reported an increase in tumors localized in the tail of the pancreas and that patients presented with much greater advancement of the disease in 2020 compared to 2019 [7], and that a delay of only 3 months for surgery in stage II or III pancreatic cancer was associated with an over 17% reduction in long-term survival [8].…”
Section: Introductionmentioning
confidence: 88%
“…Odnotowano m.in. znaczny spadek średniej liczby pacjentów rozpoczynających radioterapię [40], wydłużenie czasu od pierwszej wizyty do rozpoczęcia leczenia [41] oraz mniej wstępnych rozpoznań i rozszerzonych badań diagnostycznych i konsyliów onkologicznych [42], a także znaczne zmniejszenie liczby wykonywanych zabiegów operacyjnych [43,47] u pacjentów z chorobą nowotworową, chociaż w niektórych badaniach wskazywano na dostosowanie się systemu do zaistniałej sytuacji i stosunkowo szybki powrót do realizacji świadczeń na poziomie liczebnym sprzed pandemii [44,46]. Autorzy pracy zaznaczają konieczność prowadzenia dalszych obserwacji, aby określić długoterminowy wpływ pandemii na trendy i leczenie onkologiczne, ponieważ niekorzystne skutki mogą być opóźnione [45,46].…”
Section: Badania Dotyczące Leczenia Chorób Układu Krążeniaunclassified